2016
DOI: 10.1177/2158244015622538
|View full text |Cite
|
Sign up to set email alerts
|

Digital Library Education in Europe

Abstract: Research in digital libraries (DLs) has gained much interest across the globe. Most funding related to DL are available for building DLs, rather than producing digital librarians by developing the DL curricula and offering necessary funding to introduce state-of-the-art DL labs for future library professionals. Based on online surveys, this article investigates the status of DL education/courses in Europe, particularly, it examines the curriculum contents of DL courses, explores the future direction of library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Role of library schools in developing digital library skills of librarians The subject of digital libraries in LIS profession is receiving overwhelming attention at national and international levels (Tran and Do, 2014;Audunson and Shuva, 2016;Nguyen, 2017;Khan and Bhatti, 2017;Rafi et al, 2019;Baro et al, 2019). The demand for digital libraries and digital librarians is increasing (Baro, 2010;Rafi et al, 2019).…”
Section: Evaluation Of Digital Library Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Role of library schools in developing digital library skills of librarians The subject of digital libraries in LIS profession is receiving overwhelming attention at national and international levels (Tran and Do, 2014;Audunson and Shuva, 2016;Nguyen, 2017;Khan and Bhatti, 2017;Rafi et al, 2019;Baro et al, 2019). The demand for digital libraries and digital librarians is increasing (Baro, 2010;Rafi et al, 2019).…”
Section: Evaluation Of Digital Library Educationmentioning
confidence: 99%
“…LIS educators who teach digital libraries course need knowledge and competencies not previously associated with library work (Bury and Jamieson, 2014) and traditional education programs have not prepared staff for it. This led to increase in digital library education in different countries as shown in several studies (Nguyen and Chowdhury, 2013;Myburgh and Tammaro, 2013;Audunson and Shuva, 2016). Baro (2010) surveyed digital library education in library schools in Africa.…”
Section: Evaluation Of Digital Library Educationmentioning
confidence: 99%
“…Staff who work in DLs need knoweldge and compentieces not previousy associated with library work (Bury and Jamieson, 2014;Muhammad and Khalid, 2010) and traditional education programmes have not prepared staff for it. Recent research has shown globally the number of DLE programmes has increased (Nieuwenhuysen, 2011;Nguyen and Chowdhury, 2013;Myburgh and Tammaro, 2013;Audunson and Shuva, 2016) though none of these was in Vietnam. This research project sought to fill a gap not only in our knowledge of DLE in Vietnam but also to contribute to developments in this area that might be relevant to countries similar to Vietnam.…”
Section: The Problemmentioning
confidence: 99%
“…A number of studies have been conducted to analyze the courses of LIS [10][11][12][13], and directions of library studies in accordance with the development of IT [14][15][16]. Wyman and Imamverdiyev analyzed similarities and differences in the LIS program from 1997 to 2017 [17].…”
Section: Related Workmentioning
confidence: 99%